Enhancing the biomethane production of alkaline pre-treated lignocellulosic waste through bioaugmentation of anaerobic digestion - Van Wyk, Jamie Kate Danielle (Stellenbosch : Stellenbosch University, 2025)
van Wyk, J. K. D. 2025. Enhancing the biomethane production of alkaline pre-treated lignocellulosic waste through bioaugmentation of anaerobic digestion. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/f400411e-1961-4eb2-8606-e14d0e55e6d2